Understanding noble gas incorporation in mantle minerals: an atomistic study - Alfredo Lora; Paola Patron; Alin M. Elena; Neil L. Allan; Carlos Pinilla (Scientific Reports)
Abstract Ab initio calculations in forsterite (Mg $$_2$$ 2 SiO $$_4$$ 4 ) are used to gain insight into the formation of point defects and incorporation of noble gases. We calculate the enthalpies of incorporation both at pre-existing vacancies in symmetrically non-equivalent sites, and at interstitial positions. At high pressure, most structural changes affect the MgO $$_{6}$$ 6 units and the enthalpies of point defects increase, with those involving Mg and Si vacancies increasing more than those involving O sites. At 15 GPa Si vacancies and Mg interstitials have become the predominant intrinsic defects. We use these calculated enthalpies to estimate the total uptake of noble gases into the bulk crystal as a function of temperature and pressure both in the presence and absence of other heterovalent trace elements. For He and Ne our calculated solubilities point to atoms occupying mainly interstitial sites in agreement with previous experimental work. In contrast, Ar most likely substitutes for Mg due to its larger size and the deformation it causes within the crystal. Incorporation energies, as well as atomic distances suggest that the incorporation mainly depend on the size mismatch between host and guest atoms. Polarization effects arising from the polarizability of the noble gas atom or the presence of charged defects are minimal and do not contribute significantly to the uptake. Finally, the discrepancies between our results and recent experiments suggest that there are other incorporation mechanisms such as adsorption at internal and external interfaces, voids and grain boundaries which must play a major role in noble gas storage and solubility.